Alternagin-C binding to α2β1 integrin controls matrix metalloprotease-9 and matrix metalloprotease-2 in breast tumor cells and endothelial cells - Moritz,Milene Nóbrega de Oliveira (2018)
Abstract Background Matrix metalloproteinases (MMPs) are key players in tumor progression, helping tumor cells to modify their microenvironment, which allows cell migration to secondary sites. The role of integrins, adhesion receptors that connect cells to the extracellular matrix, in MMP expression and activity has been previously suggested. However, the mechanisms by which integrins control MMP expression are not completely understood. Particularly, the role of α2β1 integrin, one of the major collagen I receptors, in MMP activity and expression has not been studied. Alternagin-C (ALT-C), a glutamate-cysteine-aspartate-disintegrin from Bothrops alternatus venom, has high affinity for an α2β1 integrin. Herein, we used ALT-C as a α2β1 integrin ligand to study the effect of ALT-C on MMP-9 and MMP-2 expression as well as on tumor cells, fibroblats and endothelial cell migration. Methods ALT-C was purified by two steps of gel filtration followed by anion exchange chromatography. The α2β1, integrin binding properties of ALT-C, its dissociation constant (Kd) relative to this integrin and to collagen I (Col I) were determined by surface plasmon resonance. The effects of ALT-C (10, 40, 100 and 1000 nM) in migration assays were studied using three human cell lines: human fibroblasts, breast tumor cell line MDA-MB-231, and microvascular endothelial cells HMEC-1, considering cells found in the tumor microenvironment. ALT-C effects on MMP-9 and MMP-2 expression and activity were analyzed by quantitative PCR and gelatin zymography, respectively. Focal adhesion kinase activation was determined by western blotting. Results Our data demonstrate that ALT-C, after binding to α2β1 integrin, acts by two distinct mechanisms against tumor progression, depending on the cell type: in tumor cells, ALT-C decreases MMP-9 and MMP-2 contents and activity, but increases focal adhesion kinase phosphorylation and transmigration; and in endothelial cells, ALT-C inhibits MMP-2, which is necessary for tumor angiogenesis. ALT-C also upregulates c-Myc mRNA level, which is related to tumor suppression. Conclusion These results demonstrate that α2β1 integrin controls MMP expression and reveal this integrin as a target for the development of antiangiogenic and antimetastatic therapies.